Extraovarian juvenile granulosa cell tumor in a prepubertal child: novel location of a rare tumor. (16th November 2020) - User, İdil Rana and Ardıçlı, Burak and Yalçın, Bilgehan and Orhan, Diclehan and Müngen, Eren and Özcan, Nursun and Ekinci, Saniye
Abstract: Juvenile granulosa cell tumor (JGCT) is the most common type of sex cord stromal tumor arising from gonadal structures of children and young adults. We present a 3.5-year-old girl with JGCT located in retroperitoneum without ovarian involvement. Extragonadal occurrences of other sex cord stromal tumors have been rarely reported, but this is the first case of JGCT in an extragonadal location. We speculate the possible underlying mechanism of sex cord stromal tumor formation in extragonadal locations. Furthermore, clinical presentation, differential diagnosis and management of this tumor in childhood are discussed.